INNOVATIONS IN TEACHING LISTENING SKILLS FOR IELTS AND CEFR: EMBRACING MODERN METHODS (American Journal of Interdisciplinary Research and Development, 2024)
This article delves into progressive strategies for improving listening skills tailored for IELTS and CEFR exams. It highlights the integration of technology, authentic materials, interactive activities, and self-assessment to enhance comprehension.